2021
DOI: 10.1017/jfm.2021.1072
|View full text |Cite
|
Sign up to set email alerts
|

Viscoacoustic squeeze-film force on a rigid disk undergoing small axial oscillations

Abstract: This paper investigates the air flow induced by a rigid circular disk or piston vibrating harmonically along its axis of symmetry in the immediate vicinity of a parallel surface. Previous attempts to characterize these so-called ‘squeeze-film’ systems largely relied on simplifications afforded by neglecting either fluid acceleration or viscous forces inside the thin enclosed gas layer. The present viscoacoustic analysis employs the asymptotic limit of small vibration amplitudes to investigate the flow by syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…For typical SFL systems (Matsuo et al., 2000; Yoshimoto et al., 2013; Zhao, 2010), the squeeze film is slender, , whereby the tilt angle is small, ; the characteristic wavelength of the flexural oscillations is comparable to , whereby any lateral displacement of points on the deforming plate surface is negligible; and the transport speed is negligibly small (Ide et al., 2007) compared with the characteristic speed of steady gaseous streaming in the film: (Ramanarayanan, Coenen, & Sánchez, 2022). …”
Section: Problem Definitionmentioning
confidence: 99%
See 3 more Smart Citations
“…For typical SFL systems (Matsuo et al., 2000; Yoshimoto et al., 2013; Zhao, 2010), the squeeze film is slender, , whereby the tilt angle is small, ; the characteristic wavelength of the flexural oscillations is comparable to , whereby any lateral displacement of points on the deforming plate surface is negligible; and the transport speed is negligibly small (Ide et al., 2007) compared with the characteristic speed of steady gaseous streaming in the film: (Ramanarayanan, Coenen, & Sánchez, 2022). …”
Section: Problem Definitionmentioning
confidence: 99%
“…the transport speed is negligibly small (Ide et al., 2007) compared with the characteristic speed of steady gaseous streaming in the film: (Ramanarayanan, Coenen, & Sánchez, 2022).…”
Section: Problem Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melikhov et al [19] developed a viscoacoustic model and identified the different operating regimes for air squeeze films as a function of the levitation height, confirming a purely viscous regime for typical squeeze film levitation systems. Ramanarayanan et al [20] proposed another unified theory which described critical parametric conditions that causes levitation forces to switch to adhesion forces in air squeeze film systems. Remarkably, in the incompressible limit, their formulation predicted only weak adhesive squeeze film forces, adding even more uncertainty around the behaviour of incompressible squeeze films.…”
mentioning
confidence: 99%